Medieval times guilds and trade. (Coronet Instructional Films, 1965)
Scenes in Germany, Italy, Belgium, England, France, and Spain illustrate trade in the medieval world. The rise of the Venetian and Genoan merchant princes, the formation and spread of the merchant guilds, and the economic role of craft guilds in medieval society are shown. Medieval guilds and trade are compared with the European Common Market.